Pengalaman Komunikasi Ibu dengan Anak Down Syndrome Berprestasi di Masa Pandemi Covid-19 - Shofura Nur Adilah; Purwanti Hadisiwi; Ditha Prasanti (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2022)
The Covid-19 pandemic is a new situation and condition which brings a lot of changes, mothers with Down syndrome children certainly also feel their own experiences during this pandemic. The purpose of this study was to find out the meaning of a child with Down syndrome in the mother's life, and how mothers with Down syndrome children manage the activities and activities they face during Covid-19. This study uses a qualitative phenomenological approach. Data was collected by means of in-depth interviews and documentation with a total of five informants. The results obtained indicate that: 1) The meaning of a child with Down syndrome for mothers is formed from the experience of mothers having a child with Down syndrome, namely as an experience of a spiritual journey, a source of learning, and as a complement to life. 2) There are various efforts by mothers with children with Down syndrome to manage activities and activities during Covid-19, including managing children's school activities, managing children's activities & activities, and managing children's behavior, independence, & responsibilities while at home.